Menstrual characteristics and associated physical activity in some school adolescent girls in Taiz city, Yemen - د /سميرة الخليدي; د/ ماهر خالد السقاف (Taez University, 2022)
Background: Onset of menstruation is the most marked physical change in an adolescent girl. Besides secondary sexual characters, other physical changes such as weight gain, acne etc. may be problematic to young girls. This study was carried out to study the characteristics of menstrual cycles and associated physical problems among the in some adolescent school girls. Methods: A predesigned questionnaire was administered to students of classes 6 to 12 at one urban schools (Saba primary and secondary school for girls) during the period from 1st January 2021 to 1st of march 2021 in Taiz. SPSS v 23 was used for date analysis. Results: 500 students were enrolled in this study, 67.7% (338) of them were in primary school while the rest of them 32.4% (162) were from secondary school. The mean age of the girls was 16.4 years [range: 12-25; SD: 1.3]. Of these, the mean age of menarche being 13.2 years [range: 9-18; SD: 1.2]. The majority (71.2%) of them had regular menstrual pattern. Most of them suffered from moderate dysmenorrhoea (41%); nearly 34.2% reported severe dysmenorrhoea while 4.2% girls reported absence of dysmenorrhea. Only 8.6% of adolescent girls had consulted a doctor for symptoms related to menstrual. Among other physical changes besides secondary sexual characters, 58% suffered from acne, 24.2% reported weight gain and 21.6% had excessive hair growth. Conclusions: A good proportion of school going adolescent girls experience menstrual pattern deviation from normal and all so other problems such as acne, weight gain and excessive body hair. However, only a minority of them approach doctors for alleviation of these problems